IDENTIFIKASI POHON PLUS DI KECAMATAN LUMBAN JULU KPHL MODEL UNIT XIV TOBA SAMOSIR - San France; Rahmawaty Rahmawaty; Mohammad Basyuni (Peronema Forestry Science Journal, 2016)
The need for quality seed source is found to be a very important thing today, a lot of land rehabilitation work to be performed due to the large number of illegal logging and deforestation. The need for quality seeds which can be used as a seed source for the development of land rehabilitation. This study aimed to identify the source of the seeds in the form of seed gardens in the area of model XIV Toba Samosir ​​Protection Forest Management Unit, Lumban Julu Sub-District. This research was conducted from March to August 2015. Scoring method of plus trees , and  0.04 % of sampling intensity were used in this research , with a total area of ​​3761 Ha in the observation plots can be as much as 38 Plot observation, with a distance of each plots was 300 meters and each plot measuring 20 m x 20 m. Microsoft Excel were used in this research. The Results  showed 15 individuals was identified as plus trees, they are 8 Pine (Pinus merkusii), among of them was found 3 was  identified in Motung Village, 5 was in Pasar Lumban Julu Village. Furthermore 3 was Jelutung trees (Dyera costulata), 1 was identified in Jangga Dolok Village, 2 was in Pasar Lumban Julu Village, and then 4 was Puspa trees (Schima walichii), 1 was identified in Jangga Dolok Village. and 3 was in Pasar Lumban Julu Village.Keywords: Forest Management Unit, Plus Trees, Scoring Method, Seed, Toba Samosir